Analysing and modelling the impact of habitat fragmentation on species diversity: a macroecological perspective - Thomas Matthews (Frontiers of Biogeography)
My research aimed to examine a variety of macroecological and biogeographical patterns using a large number of purely habitat island datasets (i.e. isolated patches of natural habitat set within in a matrix of human land uses) sourced from both the literature and my own sampling, with the objective of testing various macroecological and biogeographical patterns. These patterns can be grouped under four broad headings: 1) species–area relationships (SAR), 2) nestedness, 3) species abundance distributions (SADs) and 4) species incidence functions (function of area). Overall, I found that there were few hard macroecological generalities that hold in all cases across habitat island systems. This is because most habitat island systems are highly disturbed environments, with a variety of confounding variables and ‘undesirable’ species (e.g. species associated with human land uses) acting to modulate the patterns of interest. Nonetheless, some clear patterns did emerge. For example, the power model was by the far the best general SAR model for habitat islands. The slope of the island species–area relationship (ISAR) was related to the matrix type surrounding archipelagos, such that habitat island ISARs were shallower than true island ISARs. Significant compositional and functional nestedness was rare in habitat island datasets, although island area was seemingly responsible for what nestedness was observed. Species abundance distribution models were found to provide useful information for conservation in fragmented landscapes, but the presence of undesirable species substantially affected the shape of the SAD. In conclusion, I found that the application of theory derived from the study of true islands, to habitat island systems, is inappropriate as it fails to incorporate factors that are unique to habitat islands.